Respuesta :

Answer:

(-1,-5)

Step-by-step explanation:

So we have the system:

y=3x-2

x-y=4.

We are asked to use substitution. Luckily, it is already setup for this because one of the equations has one of the variables solved for, namely the y=3x-2 equation.  We are going to insert y=3x-2 into x-y=4 and solve for x.

x-y=4  (with y=(3x-2) ):

x-(3x-2)=4

Distribute:

x-3x+2=4

Combine like terms:

-2x+2=4

Subtract 2 on both sides:

-2x    =2

Divide both sides by -2:

 x     =-1

Now if y=3x-2 and x=-1, then y=3(-1)-2=-3-2=-5.

So the solution is (-1,-5).